2002
DOI: 10.1055/s-2002-22040
|View full text |Cite
|
Sign up to set email alerts
|

Beschäftigungslage von Schizophrenie- und Affektkranken

Abstract: Results raise the question of deficits in providing with sheltered employment opportunities for the mentally ill and in particular for people suffering from affective disorders. Alternatives to these deficits are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…In addition, the type of diagnosis is associated with differences in types of employment. Rüesch et al (2002) examined the occupational outcomes of individuals with schizophrenic or affective disorders and found that in-patients with schizophrenia are over-represented in sheltered employment, whereas a higher proportion of in-patients suffering from an affective disorder was found in unpaid employment-like activities such as education, child-care or housework.…”
Section: The Effect Of Diagnoses and Timing Of Onsetmentioning
confidence: 99%
“…In addition, the type of diagnosis is associated with differences in types of employment. Rüesch et al (2002) examined the occupational outcomes of individuals with schizophrenic or affective disorders and found that in-patients with schizophrenia are over-represented in sheltered employment, whereas a higher proportion of in-patients suffering from an affective disorder was found in unpaid employment-like activities such as education, child-care or housework.…”
Section: The Effect Of Diagnoses and Timing Of Onsetmentioning
confidence: 99%
“…Zusatzinformationen zu den Basisdaten und zum sozialen Funktionsniveau der Befragten waren als ärztliche Fremdangaben verfügbar (Rüesch et al 2002). Zusatzinformationen zu den Basisdaten und zum sozialen Funktionsniveau der Befragten waren als ärztliche Fremdangaben verfügbar (Rüesch et al 2002).…”
Section: Fragestellung Und Hypothesenunclassified